Dupilumab Improves Endoscopic Features in Adult and Adolescent Patients With Eosinophilic Esophagitis: Post Hoc Analysis of LIBERTY EoE TREET Study - Evan S. Dellon; Margaret H. Collins; Kathryn Peterson; Xian Sun; Bram P. Raphael; Margee Louisias; Allen Radin (Clinical and Translational Gastroenterology, 2026)
INTRODUCTION: Endoscopic features are critical for monitoring treatment response in eosinophilic esophagitis (EoE). This post hoc analysis assessed dupilumab’s efficacy on endoscopic features of EoE in adults and adolescents in the phase 3 LIBERTY EoE TREET study (NCT03633617). METHODS: Data were pooled from 2 study arms in which patients with active EoE were randomized to dupilumab 300 mg weekly or placebo for 24 weeks (Parts A/B), followed by dupilumab 300 mg weekly to week (W) 52 (Parts A–C/B–C). EoE Endoscopic Reference Score (EREFS) and subscores (inflammatory and fibrostenotic) were calculated at baseline, W24, and W52 based upon worst observed region (WOR), the approach recommended for clinical settings. RESULTS: At W24, patients showed greater improvement with dupilumab vs placebo in EREFS WOR total score (least squares mean difference [95% confidence interval] –2.17 [–2.59, –1.75], inflammatory subscore –1.65 [–1.96, –1.35], and fibrostenotic subscore –0.50 [–0.71, –0.29], all P < 0.0001) and individual EREFS WOR components. The proportions of patients achieving endoscopic remission (≤2) and endoscopic normalization (0) in EREFS WOR total score, and endoscopic normalization in inflammatory and fibrostenotic subscores, were greater with dupilumab vs placebo. Improvements were maintained to W52. Dupilumab showed improvements in EREFS WOR scores vs placebo across endoscopic phenotypes (inflammatory and mixed inflammatory/fibrostenotic). DISCUSSION: Dupilumab improved endoscopic inflammatory and fibrostenotic features of EoE and led to normalization of endoscopic features compared with placebo at W24. Improvements with dupilumab were sustained to W52.